The epidemiology of Theileria parva infections on smallholder dairy farms in Kenya - Gitau, G.K.; McDermott, John J.; Katende, J.M.; Perry, Brian D. (Wiley, 2000)
The purpose of the study was to characterize the differences in epidemiology (risks of infection. morbidity. mortality) and potential control of East Coast fever (ECF) between the selected strata. Evidence of Theileria parva infection was assessed by increased antibody levels as measured in an indirect ELISA test by the percent positivity (PP) of serum samples relative to a strong positive reference serum. A prospective cohort study was conducted in five purposively sampled agroecological zone (AEZ)-grazing system strata in Murang’a District. Kenya, between March 1995 and June 1996. The study strata were selected to represent the widest range of ECF risks in the district and included, zero-grazing and open-grazing farms in the Upper Midlands (UM) one and four AEZs and zero-grazing farms in the UM2 AEZ. In total. 225 calves from 188 smallholder farms were examined from birth to age six months. Calves were recruited into the study at birth and visited within the first two weeks of life and thereafter at biweekly intervals for up to 14 visits. Important differences were observed between the different AEZ-grazing strata. Seroconversion risks of T. parva were highest in the UM4-open grazing stratum. Antibody prevalence in adult cattle and ECF morbidity and mortality risks were also highest in this stratum. In the open-grazing strata, particularly in the lower elevation AEZ, UM4, there was stronger challenge and a greater impact of ECE. There is likely to be an expansion of smallholder dairy farming into this area so that it is likely to be the most important target production system for ECF control in the central highlands of Kenya.